Development of History Teaching Materials on Islamization Subjects Based on Historical Relics of the Great Mosque of Demak - Zahra, Fathimah (Indonesian Journal of History Education, 2018)
This study aims to explore the development of historical empathy in learning global diversity through qualitative research using a literature review method. The study identifies the formulation of the problem, selects relevant research, and maps the data to compile and report results. Findings define historical empathy and its role in shaping global diversity, proposing learning models like introduction, investigation, display, and reflection. Recommended resources include films or museum visits, tailored to specific learning materials. This research offers implications for history teachers to enhance students' historical empathy skills, emphasizing global diversity to foster tolerant, democratic, open-minded, and critical-thinking students. The study highlights the development of teaching materials integrating Islamic history and the Great Mosque of Demak, demonstrating improved student engagement, analytical skills, and cognitive outcomes through research and development methodology.